Peran Brand Image dalam Memediasi Pengaruh Electronic Word of Mouth (E-Wom) Terhadap Purchase Intention: Studi Kasus pada Produk Smartphone Iphone di Kota Denpasar - Christian Wisnu Gunawarman Siwu; Gede Bayu Rahanatha (Jurnal Visi Manajemen, 2025)
This research aims to analyze the role of brand image as a mediating variable in the relationship between electronic word of mouth (e-WOM) and purchase intention for iPhone smartphone products in Denpasar City. The study is grounded in Consumer Behavior Theory, which explains how external and internal factors influence purchasing decisions. The widespread use of e-WOM in the digital age is a significant external factor in shaping consumer perceptions. Conversely, brand image is a critical internal asset for a company to build customer trust and loyalty. By understanding the interaction among these three variables, this research is expected to provide strategic insights for marketers. The study’s population includes Denpasar residents who either use or intend to purchase an iPhone smartphone. The sample size is 100 individuals, selected using a purposive sampling technique based on specific criteria such as age, social media usage, and knowledge of iPhone products. Data was collected by distributing questionnaires to respondents. The data analysis methods used were descriptive and inferential analysis. Inferential analysis included the Classical Assumption Test to ensure the data met statistical requirements, Path Analysis to examine the direct and indirect relationships between variables, the Sobel Test to measure the significance of the mediation effect, and the Variance Accounted For (VAF) Test to determine the extent to which brand image mediates the relationship. The results show that brand image plays a partial mediating role in the effect of e-WOM on purchase intention. This indicates that e-WOM not only directly influences purchase intention but also indirectly through the formation of a positive brand image. This finding confirms the importance of brand image as a bridge connecting electronic word-of-mouth promotion with consumers’ purchasing decisions. The implications of this research are highly relevant for iPhone smartphone marketers.